The Effects of the Width of an Isolated Valley on Near-Surface Turbulence - Sylvio Freitas; Frank Harms; Bernd Leitl (Atmosphere, 2021)
With the aim of ascertaining the effects of the widths (<semantics>A</semantics>) of valleys on near-surface turbulence, flows over an isolated symmetric three-dimensional valley of constant depth (<semantics>H</semantics>) and slopes are characterized in a large-boundary-layer wind tunnel. Starting at A = 4H, valley widths were systematically varied to A = 12H with constant increments of 2H. High-resolution laser-Doppler velocimetry measurements were made at several equivalent locations above each of the resulting valley geometries and compared with data from undisturbed flows over flat terrain. Flow separation caused by the first ridges generated inner-valley recirculation bubbles with lengths dependent on the valley widths. Secondary recirculation zones were also observed downstream from the crests of the second ridges. Results show that the width modifications exert the strongest effects on turbulence within the valleys and the vicinities of the second ridges. Above these locations, maximal magnitudes of turbulence are generally found for the larger width geometries. Furthermore, lateral turbulence overpowers the longitudinal counterparts nearest to the surface, with maximal gains occurring for the smaller widths. Our data indicate that valley widths are impactful on near-surface flows and should be considered together with other more established geometric parameters of influence.